Forensic psychiatry in Finland: an overview of past, present and future - Allan Seppänen (International Journal of Mental Health Systems, 2020)
Abstract Despite a recent contrary trend, Finland has been for decades one of the most violent countries in Western Europe. Also, Finland has had one of the highest number of psychiatric beds per capita in Europe, although this, too, has seen a sharp decline. Against this background, among other national idiosyncrasies, Finland has developed its forensic psychiatric services. Here, we describe the legal, organizational and clinical structure of these services, and outline the historical and current issues that have shaped them. Finally, we consider future challenges facing the Finnish forensic service system, as part of wider European and global trends.